PENGARUH MODEL BRAIN-BASED LEARNING TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA DAN EFIKASI DIRI SISWA KELAS IV SD - Himawan, Yogi (JURNAL ILMIAH EDUNOMIKA, 2024)
This study aims to examine the effect of Brain-Based Learning (BBL) model on the ability to solve mathematical problems and self-efficacy of fourth grade elementary school students. The background of this study is based on the low ability to solve mathematical problems and self-efficacy of students in some elementary schools, as well as the limitations of the learning model applied today. This study uses a quantitative approach with quasi-experimental methods and Pretest-Posttest only Control Group Design. Subjects consisted of fourth grade elementary school students in Cilongok District, Banyumas, with samples taken from 4 elementary schools that apply the Independent curriculum using cluster random sampling technique. The BBL Model is applied to the experimental class, while the control Class uses the direct instruction method. The Data were collected through mathematical problem solving ability test and self-efficacy questionnaire, then analyzed using normality test, homogeneity test, and Independent Sample t-Test. The results showed that the BBL model has a significant effect on improving the ability to solve mathematical problems (count = 5.613, p = 0.000) and student self-efficacy (count = 5.195, p = 0.000). Thus, the application of the BBL model proved effective in improving both aspects in the fourth grade of elementary school students.